Separating Abram and Lot : the narrative role and early reception of Genesis 13 - Rickett, Daniel (Arts and Archaeology of the Islamic World, 2020)
In Separating Abram and Lot: The Narrative Role and Early Reception of Genesis 13, Dan Rickett presents a fresh analysis of two of Genesis' most important characters. Many have understood Lot as Abram's potential heir and as an ethical contrast to him. Here, Rickett explores whether these readings best reflect the focus of the story. In particular, he considers the origin of these readings and how a study of the early Jewish and Christian reception of Genesis 13 might help identify that origin. In turn, due attention is given to the overall purpose of Genesis 13, as well as how Lot and his function in the text should be understood.